DOI: 10.3990/1.9789036552844
|View full text |Cite
|
Sign up to set email alerts
|

IoT as Simple as Do Re Mi: A micro-configurational approach to the social context of Internet of Things skills and digital inequalities

Abstract: v a n d e r z e e u w , a . (2021) IoT as Simple as Do Re Mi. A micro-figurational approach to the social context of IoT skills and digital inequalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 137 publications
0
3
0
Order By: Relevance
“…In the studies by van der Zeeuw et al ( 11 , 12 ), the authors study the digital divide and (lack of) digital literacy in the Internet-of-Things (IoT) context. TIIM was used in combination with interview data as a diary study instrument to study socio-contextual dispositions as to why some people can better capitalize on IoT benefits creatively than others among 30 households.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the studies by van der Zeeuw et al ( 11 , 12 ), the authors study the digital divide and (lack of) digital literacy in the Internet-of-Things (IoT) context. TIIM was used in combination with interview data as a diary study instrument to study socio-contextual dispositions as to why some people can better capitalize on IoT benefits creatively than others among 30 households.…”
Section: Resultsmentioning
confidence: 99%
“…Published studies report on key elements of the platform. Specifically, custom question types and mobile questionnaires are used in van der Zeeuw’s study ( 11 ). Kip et al ( 22 ) demonstrated the usage of TIIM for rapid prototyping in the mental health domain.…”
Section: Resultsmentioning
confidence: 99%
“…the IoT system and the woman is merely a co-user (e.g., Geeng et al, 2019;Rode & Poole, 2018;Van der Zeeuw, 2021). This distribution of roles, which is more 6 pronounced in less educated households (Giani, Hope, & Skorge, 2022), could lead to digital inequality in which men gain more advantages from the IoT than women do, regardless of their skills.…”
mentioning
confidence: 99%